Power and temporal commitment preference: an investigation in Portugal, Turkey, and the United States - Armagan, Sungu (2011)
The current research explores the impact of power on temporal commitment preference (an individual’s preference for shorter or longer time durations for agreements in decision making situations) across three countries: Portugal, Turkey, and the United States. A pilot study (N = 356) established cultural differences in uncertainty avoidance, which was expected to impact choices and behaviors involving power and temporality. The main study (N = 433) investigated the relationship between power and temporal commitment preference. Across all countries, high power individuals preferred shorter temporal commitments than low power individuals. In addition, the U.S. participants preferred longer temporal commitments than either the Portuguese or Turkish participants. We argue that differences in uncertainty avoidance help explain some of the differences in individuals’ temporal commitment preferences across diverse cultural settings. Implications for practice and future directions are also discussed.